Analisis Torsi Motor Bakar 4 Langkah Berbahan Bakar LPG dengan Beda Sudut Pengapian - Puji Kristianto; Nasrul Ilminnafik; Mochamad Edoward Ramadhan (STATOR: Jurnal Ilmiah Mahasiswa Teknik Mesin, 2018)
The use of LPG fuel is an alternative to the use of environmentally friendly gasoline. The use of LPG fuel causes a decrease in motor performance, which is due to the different characteristics of combustion between LPG and gasoline. This can be overcome by rearranging the ignition timing corresponding to the LPG burning characteristics. This study aims to obtain data comparing the performance of combustion engine 4 step LPG fuel with variations of different ignition angle and gasoline fuel at the ignition angle standard. This research was conducted with two tests, the test with variation of different angle of LPG fuel and standard test on motorcycles Honda Astrea Prima 100 cc in 1991. From result of research of maximum torque produced by LPG fuel bigger than gasoline fuel. The advanced ignition angle (180 BTDC) is the most optimal angle of ignition resulting in maximum torque than at any other ignition angle. Keywords: LPG, Ignition Corner, and Torque.